Persepsi Mahasiswa terhadap Nilai Moderasi Beragama dalam Film Walid: Telaah Kritis Perspektif Pendidikan Islam - Choirun Nisa; Naura Afkarina; Hidayah, Ulil (RABBAYANI: Jurnal Pendidikan dan Peradaban Islami, 2025)
Religious moderation is a fundamental principle in fostering harmonious religious life within Indonesia's plural society. Islamic education holds a strategic role in instilling these values, particularly in the digital era dominated by visual media and shifting learning patterns. This study aims to analyze the perceptions of Islamic Education students toward the representation of religious moderation in the Walid movie, and to assess the role of Islamic education in shaping a moderate religious worldview. Using a qualitative case study approach, data were collected through in-depth interviews with students who had watched the movie of Walid. The findings reveal that Walid serves as a reflective medium that enhances critical awareness of the importance of religious moderation. However, the film also carries the risk of misinterpretation not supported by adequate religious and media literacy. Islamic education is perceived as a central force in forming a balanced understanding of religious issues, serving as a bulwark against both extremism and interpretive liberalism. The study concludes the necessity of integrating contextual Islamic education curricula and media literacy as strategies to cultivate a generation that is religiously moderate, critical, and inclusive.